2017
DOI: 10.1016/j.ijid.2017.07.024
|View full text |Cite
|
Sign up to set email alerts
|

First serological evidence of Crimean-Congo haemorrhagic fever in febrile patients in Mozambique

Abstract: This study shows for the first time that humans are exposed to CCHFV in Mozambique. It highlights the need for further work to investigate the broader extent of circulating CCHFV in the country and its clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…The CCHFV exposure rate of 4.4% in this study was unexpectedly higher than those originally reported as being of 0.0% to 0.5% [ 5 , 6 ]. An anti-CCHFV IgG rate of 2.7% was recently reported in an urban setting in Maputo, Mozambique [ 15 ]. The relatively higher rates of the population exposure to RVFV and CCHFV, compared to those reported by “historical” studies in Cameroon [ 5 , 6 ], could be associated to several factors differentiating the past and present studies.…”
Section: Discussionmentioning
confidence: 99%
“…The CCHFV exposure rate of 4.4% in this study was unexpectedly higher than those originally reported as being of 0.0% to 0.5% [ 5 , 6 ]. An anti-CCHFV IgG rate of 2.7% was recently reported in an urban setting in Maputo, Mozambique [ 15 ]. The relatively higher rates of the population exposure to RVFV and CCHFV, compared to those reported by “historical” studies in Cameroon [ 5 , 6 ], could be associated to several factors differentiating the past and present studies.…”
Section: Discussionmentioning
confidence: 99%
“…African countries from which CCHF has been reported include Burkina Faso, Central Africa Republic, Democratic Republic of Congo, Egypt, Kenya, Mauritania, Namibia, Nigeria, South Africa, Senegal, Sudan, Tanzania, and Uganda 1,[7][8][9][10][11][12][13][14][15][16] and countries yet to report CCHF but with evidence of viral circulation either from serological surveys or CCHFV isolation from ticks include Algeria, Benin, Cameroon, Equatorial Guinea, Ethiopia, Ghana, Guinea, Mali, Madagascar, Morocco, Mozambique, Niger, Somalia, Tunisia, and Zimbabwe. 1,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] The presence of CCHFV in Somalia was suggested after evidence of the CCHFV in Hyalomma ticks obtained from Somali cattle and sheep exported to the United Arab Emirates. 28 In the Middle East, the disease has been described in Iran, Iraq, Saudi Arabia, Oman, and the United Arab Emirates.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, outbreaks and further cases of CCHF were reported in wide areas in countries in Africa (Uganda, South Africa, Sudan, and Mauritania), the Middle East (Iraq, United Arab Emirates, Iran, Oman, and Saudi Arabia), Europe (Bulgaria, Kosovo, Turkey, and Albania), and Asia (China, Pakistan, Afghanistan, and India) (Ergonul 2006). Serological evidence for CCHFV further suggested the potential prevalence of this virus in a wider geographic distribution including Malaysian, Nigeria, Tunisia, Sub-Saharan Africa, Iberian Peninsula (Bukbuk et al 2014(Bukbuk et al , 2016Mohd Shukri et al 2015;Muianga et al 2017;Palomar et al 2017;Wasfi et al 2016). Hence, CCHFV may be more widely distributed worldwide than is currently known.…”
Section: Introductionmentioning
confidence: 99%